Transfer Teknologi Okulasi Durian di Kelompok Tani Harapan Baru I Kelurahan Batu Putuk Bandar Lampung - Sesanti, Rizka Novi; Hidayat, Hilman; Hakim, Nurman Abdul (Politeknik Negeri Lampung., 2014)
Technology transfer about durian grafting in Harapan Baru I farmers Group, Batu Putuk village, Bandar Lampung city has been done . This activity aims to improve ( 1 ) knowledge of members of Harapan Baru I Farmers Group about characteristics durian superior. ( 2 ) knowledge of members of Harapan Baru I Farmers Group in durian grafting techniques . ( 3 ) skills of members of Harapan Baru I Farmers Group in durian grafting techniques. The method used is counseling, demonstration and practice . Evaluation used is initial evaluation , final evaluation , and evaluation success durian grafting. Results of activity showed that ( 1 ) knowledge of members of Harapan Baru I Farmers Group in characteristics durian superior reached 87.06 % . (2) knowledge of members of Harapan Baru I Farmers Group in durian grafting technique reached 87.06 % . (3) Skills of members of Harapan Baru I Farmers Group in durian grafting techniques increased from 10 % to 60 % . Key words : durian, Batu Putuk, grafting